Islamic Universities Produce Moral and Innovative Leaders - Auliya Yufina; Zainap Hartati (al-Afkar, Journal For Islamic Studies, 2026)
Islamic universities have a strategic role in producing future leaders who are not only intellectually superior but also noble and innovative. This study aims to analyze PTI's efforts in integrating Islamic values and innovation through a literature review approach. The results show that moral education is the foundation for the formation of student character, while innovation is encouraged through the application of digital technology and project- based curriculum. Challenges such as global cultural influence and lack of synergy between theory and practice hinder the optimization of the program. The proposed solutions include strengthening the integration of Islamic values in the curriculum, the use of technology, and a campus environment that supports creativity. With this step, PTI is expected to produce moral and innovative leaders who are able to compete globally.